Au/nc-Si:H core–shell nanostructures prepared by hot wire assisted plasma enhanced chemical vapor deposition technique - Chan, K.W.; Goh, Boon Tong; Abdul Rahman, S.; Aspanut, Zarina (Elsevier, 2012)
In this study, Au film was embedded in Si:H film on quartz substrate with and without an SiOx layer by using the hot wire assisted plasma enhanced chemical vapor deposition (HW-PECVD) technique. The as-prepared Au/Si:H films were post-thermally annealed at 800 °C in nitrogen ambient in order to initiate the growth of Au NPs. The annealed Au/a-Si:H film deposited on quartz substrate without an SiOx layer showed the formation of well-distributed and spherical Au NPs. Formations of Au/nc-Si:H core shell nanostructures were observed on annealed film deposited on quartz substrate with an SiOx layer. XRD and micro-Raman scattering spectra revealed that the degree of crystallinity of nc-Si:H was dependent on the annealing temperature and interaction between a-Si:H film and SiOx layer. Optical spectra showed that the Au NPs on annealed films deposited on quartz substrate without an SiOx layer exhibited prominent SPR peak while annealed Au/nc-Si:H core shell nanostructures showed increased reflectance of light in the visible region.